Malacofauna on Three Plants: Cistus ladaniferus L. (Cistaceae) Juniperus oxycedrus L. (Cupressaceae) and Marrubium vulgare L. (Lamiaceae) in the Mounts of Tlemcen (North-West Algeria) - Damerdji, Amina (British Journal of Healthcare and Medical Research, 2024)
The Tlemcen region is located in northwest Algeria, whose climatic impact results in the degradation of the matorral forest, an open formation made up of plant species such as: cistaceae, lamiaceae (horehound, stoeckade lavender) and Cupressaceae (juniper...). We propose to carry out an approach to the diversity of Cistus ladaniferus (Cistaceae) Juniperus oxycedrus (Cupressaceae) and Marrubium vulgare (Lamiaceae). The malacological richness is estimated at 10 on the Cistus ladanifera, at 9 on the oxycedar juniper and at 7 on the horehound. This is distributed between 4 families: Milacidae, Sphincterochilidae, Helicidae and Subulinidae. Sphincterochila candidissima is present only on the ladaniferous cistus. Two species of Milacidae are found on the oxycedar. The 4th family includes a single species, Rumina decollata. Regarding the Helicidae family, the most diverse has 2 subfamilies: Helicinae and Helicellinae. The 1st subfamily has 6 species on the oxycedar and the gum cistus and 5 species on the horehound. The 2nd subfamily includes only one species Helicella terveri on horehound. The seasonal distribution according to the species richness of Gastropods is shown. We are looking for malacological species specific to each of the three plant species and the species that are common to them. Finally, the vertical distribution of gastropods is given.